Rapid vs. gradual changes in light significantly modulate diel photo‐acclimation strategy and can lead to changes in comparative physiology in the green algae Micromonas commoda - Shannon M. Dalessandri; Alison Siersma; Jeffrey W. Krause; Kenneth D. Hoadley (Limnology and Oceanography, 2025)
Variable chlorophyll a (Chl a ) fluorescence, a standard tool for assessing phytoplankton physiology, offers a wealth of information on photosynthetic performance and primary productivity through noninvasive means. However, a better understanding of diurnal patterns in photosynthesis is critically important as advanced fluorescence techniques are increasingly used to monitor coastal and oceanic primary productivity rates in situ. In this study, we coupled a custom‐made, Fast Repetition Rate Chl a fluorometer to an algal culture system (photobioreactor) to monitor the photosynthetic response of two strains of the green alga, Micromonas commoda , under highly regulated light and CO 2 conditions. When comparing diel profiles, our results reveal notable differences in the quantum yield of PSII and reoxidation kinetics across light patterns despite exposure to the same integrated photon dose per day. Specifically, CCMP2709 experienced a larger reduction in the quantum yield of PSII during the dark period, likely reflecting elevated chlororespiratory activity. This suggests that diel light patterns with rapid shifts in irradiance can bias phytoplankton toward the use of alternative electron pathways; such shifts can alter energetic budgets thereby leading to physiological changes. Our results also indicate a light‐profile dependent response to elevated CO 2 conditions, as reductions in cell size, relative Chl a fluorescence per cell, and side scatter are observed under the gradual, but not rapid changes in light intensity. These findings emphasize the utility of high‐resolution tools for monitoring photosynthetic performance in algal research, and the need to account for diel light patterns when comparing physiology among species and/or experimental conditions.

The diversity, distribution, and temporal stability of coral ‘zooxanthellae’ on a pacific reef: from the scale of individual colonies to across the host community - Allison M. Lewis; Caleb C. Butler; Kira E. Turnham; Drew F. Wham; Kenneth D. Hoadley; Robin T. Smith; Dustin W. Kemp; Mark E. Warner; Todd C. LaJeunesse (Coral Reefs, 2024)

Bio-optical signatures of in situ photosymbionts predict bleaching severity prior to thermal stress in the Caribbean coral species Acropora palmata - Kenneth D. Hoadley; Sean Lowry; Audrey McQuagge; Shannon Dalessandri; Grant Lockridge; Sibelle O’Donnell; Holland Elder; Maria Ruggeri; Eleftherios Karabelas; Courtney Klepac; Carly Kenkel; Erinn M. Muller (Coral Reefs, 2024)

A phenomic modeling approach for using chlorophyll-a fluorescence-based measurements on coral photosymbionts - Kenneth D. Hoadley; Grant Lockridge; Audrey McQuagge; K. Blue Pahl; Sean Lowry; Sophie Wong; Zachary Craig; Chelsea Petrik; Courtney Klepac; Erinn M. Muller (Frontiers in Marine Science, 2023)
We test a newly developed instrument prototype which utilizes time-resolved chlorophyll- a fluorescence techniques and fluctuating light to characterize Symbiodiniaceae functional traits across seven different coral species under cultivation as part of ongoing restoration efforts in the Florida Keys. While traditional chlorophyll- a fluorescence techniques only provide a handful of algal biometrics, the system and protocol we have developed generates > 1000 dynamic measurements in a short (~11 min) time frame. Resulting ‘high-content’ algal biometric data revealed distinct phenotypes, which broadly corresponded to genus-level Symbiodiniaceae designations determined using quantitative PCR. Next, algal biometric data from Acropora cervicornis (10 genotypes) and A. palmata (5 genotypes) coral fragments was correlated with bleaching response metrics collected after a two month-long exposure to high temperature. A network analysis identified 1973 correlations (Spearman R > 0.5) between algal biometrics and various bleaching response metrics. These identified biomarkers of thermal stress were then utilized to train a predictive model, and when tested against the same A. cervicornis and A. palmata coral fragments, yielded high correlation (R = 0.92) with measured thermal response (reductions in absorbance by chlorophyll-a). When applied to all seven coral species, the model ranked fragments dominated by Cladocopium or Breviolum symbionts as more bleaching susceptible than corals harboring thermally tolerant symbionts ( Durusdinium ). While direct testing of bleaching predictions on novel genotypes is still needed, our device and modeling pipeline may help broaden the scalability of existing approaches for determining thermal tolerance in reef corals. Our instrument prototype and analytical pipeline aligns with recent coral restoration assessments that call for the development of novel tools for improving scalability of coral restoration programs.

Different functional traits among closely related algal symbionts dictate stress endurance for vital Indo‐Pacific reef‐building corals - Kenneth D. Hoadley; Daniel. T. Pettay; Allison Lewis; Drew Wham; Chris Grasso; Robin Smith; Dustin W. Kemp; Todd LaJeunesse; Mark E. Warner (Global Change Biology, 2021)
Reef‐building corals in the genus Porites are one of the most important constituents of Indo‐Pacific reefs. Many species within this genus tolerate abnormally warm water and exhibit high specificity for particular kinds of endosymbiotic dinoflagellates that cope with thermal stress better than those living in other corals. Still, during extreme ocean heating, some Porites exhibit differences in their stress tolerance. While corals have different physiological qualities, it remains unknown whether the stability and performance of these mutualisms is influenced by the physiology and genetic relatedness of their symbionts. We investigated two ubiquitous Pacific reef corals, Porites rus and Porites cylindrica , from warmer inshore and cooler offshore reef systems in Palau. While these corals harbored a similar kind of symbiont in the genus Cladocopium (within the ITS2 C15 subclade), rapidly evolving genetic markers revealed evolutionarily diverged lineages corresponding to each Porites species living in each reef habitat. Furthermore, these closely related Cladocopium lineages were differentiated by their densities in host tissues, cell volume, chlorophyll concentration, gross photosynthesis, and photoprotective pathways. When assessed using several physiological proxies, these previously undifferentiated symbionts contrasted in their tolerance to thermal stress. Symbionts within P . cylindrica were relatively unaffected by exposure to 32℃ for 14 days, whereas P . rus colonies lost substantial numbers of photochemically compromised symbionts. Heating reduced the ability of the offshore symbiont associated with P . rus to translocate carbon to the coral. By contrast, high temperatures enhanced symbiont carbon assimilation and delivery to the coral skeleton of inshore P . cylindrica . This study indicates that large physiological differences exist even among closely related symbionts, with significant implications for thermal susceptibility among reef‐building Porites .

Moderate nutrient concentrations are not detrimental to corals under future ocean conditions - Kerri L. Dobson; Stephen Levas; Verena Schoepf; Mark E. Warner; Wei-Jun Cai; Kenneth D. Hoadley; Xiangchen Yuan; Yohei Matsui; Todd F. Melman; Andréa G. Grottoli (Marine Biology, 2021)

Correction to: High-temperature acclimation strategies within the thermally tolerant endosymbiont Symbiodinium trenchii and its coral host, Turbinaria reniformis, differ with changing pCO2 and nutrients - Kenneth D. Hoadley; D. Tye Pettay; Andréa G. Grottoli; Wei-Jun Cai; Todd F. Melman; Stephen Levas; Verena Schoepf; Qian Ding; Xiangchen Yuan; Yongchen Wang; Yohei Matsui; Justin H. Baumann; et al. (Marine Biology, 2020)

Use of Open Source Hardware and Software Platforms to Quantify Spectrally Dependent Differences in Photochemical Efficiency and Functional Absorption Cross Section within the Dinoflagellate Symbiodinium spp. - Kenneth D. Hoadley; Mark E. Warner (Frontiers in Marine Science, 2017)

Coral calcification under environmental change: a direct comparison of the alkalinity anomaly and buoyant weight techniques - Verena Schoepf; Xinping Hu; Michael Holcomb; Wei-Jun Cai; Qian Li; Yongchen Wang; Hui Xu; Mark E. Warner; Todd F. Melman; Kenneth D. Hoadley; D. Tye Pettay; Yohei Matsui; et al. (Coral Reefs, 2017)

High-temperature acclimation strategies within the thermally tolerant endosymbiont Symbiodinium trenchii and its coral host, Turbinaria reniformis, differ with changing pCO 2 and nutrients - Kenneth D. Hoadley; D. Tye Pettay; Andréa G. Grottoli; Wei-Jun Cai; Todd F. Melman; Stephen Levas; Verena Schoepf; Qian Ding; Xiangchen Yuan; Yongchen Wang; Yohei Matsui; Justin H. Baumann; et al. (Marine Biology, 2016)

Contrasting physiological plasticity in response to environmental stress within different cnidarians and their respective symbionts - Kenneth D. Hoadley; Daniel. T. Pettay; Danielle Dodge; Mark E. Warner (Coral Reefs, 2016)

Differential carbon utilization and asexual reproduction under elevated p CO 2 conditions in the model anemone, E xaiptasia pallida , hosting different symbionts - Kenneth D. Hoadley; Dana Rollison; D. Tye Pettay; Mark E. Warner (Limnology and Oceanography, 2015)
Here we report the effects of elevated p CO 2 on the model symbiotic anemone Exaiptasia pallida and how its association with three different strains of the endosymbiotic dinoflagellate Symbiodinium minutum (ITS2‐type B1) affects its response. Exposure to elevated p CO 2 (70.9 Pa) for 28 d led to an increased effective quantum yield of PSII in actinic light within two of the alga‐anemone combinations. Autotrophic carbon fixation, along with the rate of carbon translocated to the animal, were significantly elevated with high p CO 2 . Elevated p CO 2 exposure also coincided with significantly greater asexual budding rates in all tested anemones. Further, differences in photochemistry and carbon translocation rates suggest subtle differences in the response to p CO 2 among the three strains of S. minutum and their host anemones. This illustrates the potential for physiological diversity at the subspecies level for this ecologically important dinoflagellate. Positive alterations in photosynthesis, carbon utilization, and fitness within this model symbiosis suggest a potential benefit from ocean acidification (OA) not yet observed within corals, which may enable these anthozoans to gain a greater ecological presence under future OA conditions.